2023
DOI: 10.1021/acs.macromol.2c02159
|View full text |Cite
|
Sign up to set email alerts
|

Gelation in Photoinduced ATRP with Tuned Dispersity of the Primary Chains

Abstract: We investigated gelation in photoinduced atom transfer radical polymerization (ATRP) as a function of Cu catalyst loading and thus primary chain dispersity. Using parallel polymerizations of methyl acrylate with and without the addition of a divinyl crosslinker (1,6-hexanediol diacrylate), the approximate values of molecular weights and dispersities of the primary chains at incipient gelation were obtained. In accordance with the Flory–Stockmayer theory, experimental gelation occurred at gradually lower conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We attribute this difference to the closer proximity of the propagating polymer chains within the network, which could result in a higher probability of termination through intramolecular combination reactions and also the reduced efficiency of deactivation by chain transfer due to the highly viscous nature of the synthesis. 59,74 This is evidenced by a small amount of high molecular weight shouldering in the molar mass distributions of the various cleaved polymer networks (Fig. 3b) and demonstrates that analogous linear and network polymer syntheses do not yield identical materials.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…We attribute this difference to the closer proximity of the propagating polymer chains within the network, which could result in a higher probability of termination through intramolecular combination reactions and also the reduced efficiency of deactivation by chain transfer due to the highly viscous nature of the synthesis. 59,74 This is evidenced by a small amount of high molecular weight shouldering in the molar mass distributions of the various cleaved polymer networks (Fig. 3b) and demonstrates that analogous linear and network polymer syntheses do not yield identical materials.…”
Section: Resultsmentioning
confidence: 98%
“…However, to the best of our knowledge, there are only limited examples where dispersity-controlled networks have been prepared on variation of the catalyst concentration in ATRP. 59,60 Matyjaszewski and coworkers demonstrated that decreasing copper concentration in activator regenerated by electron transfer (ARGET) ATRP resulted in a higher primary chain dispersity and an earlier gel point. 60 However, the primary chain dispersity of the resulting networks was not measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be defined as strongest materials or materials most capable of swelling with solvent, which has been connected to overall network uniformity [14,58] . Indeed, this is an unusual result, because in general RDRP methods lead to more uniform networks than their FRP counterparts due to the control over the primary chain structure [14,59–62] . This highlights the importance of control over the primary chain dispersity when designing polymer materials.…”
Section: Resultsmentioning
confidence: 99%
“…where vc is the weight-average number of crosslinks per primary chain (equal to 1 at incipient gelation) and ρc is the fraction of crosslinked units. 22,51,52 Hence, only very few crosslinked units (ρc ≥ 1/DPw) are necessary to reach the gel point for the typical DPw values.…”
Section: Reverse Gel Point Modelmentioning
confidence: 99%